Perspectives in meat processing. (September 2019) - Vasilev, D; Stajkovic, S; Karabasil, N; Dimitrijevic, M; Teodorovic, V
Abstract: Meat technology includes all steps from animal handling and slaughtering to production of different meat products. During animal handling, special attention is paid to animal welfare, not only to protect animals from suffering but also because of animal welfare's importance for meat quality. The oldest processing methods (chilling, freezing, salting, smoking and drying) are being readjusted with respect to equipment and consumer's health issues. Special attention is given to preservation of meat's nutritive value (milder heat treatment) and health promoting properties of the products (functional foods). Novel methods (irradiation, high pressure, pulsed electric field, pulsed light and cold plasma) struggle with some issues such as acceptance by consumers, expensive equipment and effects on food's sensory properties. Along with novel products, demand for traditional meat products is still increasing which requires the the uniqueness and quality of these products to be preserved, along with increased production capacity.